(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The subject of Arab Investment abroad, and how to return them to the Arab countries, Was given a great interest by economists and specialists, Specially because of the value and the volume of these investment are very large, and incase of relocation and employment in the Arab countries, they can achieve such rates of economic growth and development of an unprecedented.